Training of Fertilizer Application Methods For Coffee Farmers in Gampong Paya Guci, Tangse District - Muliana, Muliana; Syafri, Yulia; Yusra, Yusra (LPPM Universitas Malikussaleh, 2023)
Paya Guci is a village located in Tangse District, Pidie District, Aceh Province. 75% of the population's livelihood as farmers. Tangse became the center for Liberika coffee (kupi panah) in Aceh. Liberika coffee the early 19th century was brought to Tangse by the Dutch. One of the factors to support crop productivity is through fertilization, but the Gampong Paya coffee farmers have relatively never fertilized their coffee plants. Therefore, we need